Effect of nanoclay addition on physical, chemical, optical and biological properties of experimental dental resin composites. Issue 3 (March 2017) - Munhoz, Tais; Fredholm, Yann; Rivory, Pascaline; Balvay, Sandra; Hartmann, Daniel; da Silva, Pedro; Chenal, Jean-Marc
Highlights: Montmorillonite can be successfully functionalised by a methacrylate-based compound with an increase of interlayer space from 11.6 Å to 14.2 Å. Dental resin composites can be prepared by mixing organically modified montmorillonite, barium glass and a methacrylate matrix. Substitution of clay results in higher storage modulus as observed by DMA. Clays may have a barrier effect to monomers release as observed in HPLC analysis and biological tests. Clays interfere with light transmittance as observed in spectrometry, water sorption and Vickers hardness. Abstract: Objective: To prepare organically modified montmorillonite (OM MMT) and assess mechanical, physical, chemical and biological effects of its introduction into resin-composites. Methods: Natural MMT clay was modified by a methacrylate functionalized quaternary ammonium intercalating agent. Interlayer distance was measured by X-ray diffraction. Dental composites were then prepared with x = 0, 1, 2.5, 5 or 7.5 wt.% of OM MMT, (75 − x) wt.% of silanated barium glass and 25 wt.% of methacrylate based matrix). Relative weight loss was measured and the effect of the substitution on mechanical properties was studied by dynamic mechanical analysis and hardness tests. Properties of resin composites were evaluated in terms of water sorption, light transmittance, biological tests and by high-performance liquid chromatography (HPLC). Results: Resin based composites with well-dispersed organically modified MMT were successfully prepared. There were no significant weight loss differences shown by TGA within all samples. The DMA analysis showed that the introduction of clays have a beneficial effect in increasing the storage and elastic modulus of composites. Clay presence was shown to interfere with the blue light transmittance, affecting Vickers hardness and water sorption levels. The amount of released monomers measured from extracts was below expected levels for this type of materials and biological tests show satisfactory cell compatibility. Significance: This paper reports the successful functionalization of MMT by a methacrylate group and further incorporation in experimental dental composites. Physical and biological results show a potential interest to the application of nanoclays into dental resin composites.